La enseñanza y el aprendizaje de los conectores contraargumentativos en español como lengua extranjera. El uso del CORPUS de alumno - Górska, Weronika (Investigationes Linguisticae, 2006)
The present article is a part of M.A. thesis completed and defended in the Institute of Linguistics at Adam Mickiewicz University in Poznań (June 2006). The main focus of the work is the presentation of the application of analysis of the student corpus in the examination of the mastering of the connectors of contrargumentation. The base for the work is being formed by a corpus of 300 pages. The material has been created by the author who would get information via forum La ruta de la lengua Espanola, where information are being transferred between Spanish people – future teachers of their native language, and the students of Spanish from abroad. The text contains introduction to the linguistics of the corpus, methodology of its creation as well as analysis and comparison to the standard corpus of the Spanish language.